Are you my baby? Testing whether paternity affects behavior of cobreeder male acorn woodpeckers. (10th June 2021) - Koenig, Walter D; Prinz, Anna C B; Haydock, Joseph; Dugdale, Hannah L; Walters, Eric L
Abstract: Natural selection is expected to favor males that invest more in offspring they sire. We investigated the relationship between paternity and male behavior in the acorn woodpecker ( Melanerpes formicivorus ), a cooperative breeder that lives in family groups including offspring that remain on their natal territory, sometimes for years, and cobreeders of both sexes. Regardless of group composition, only one communal nest is attended at a time. Whereas cobreeding females share maternity equally, one male usually sires the majority of young in the group's communal nest. Copulations are rarely observed, and thus it has not been possible to link paternity to sexual behavior. There were no differences among cobreeder males that did or did not sire young in their propensity to roost in the nest cavity at night. However, cobreeder males that attended females continuously prior to egg-laying were more likely to successfully sire young than males that did not, and the relative share of feeding visits and time spent at the subsequent nest were positively related to a male's realized paternity. These differences in male behavior were partly due to differences among males and partly to plasticity in male behavior covarying with paternity share. Feedings by males successfully siring young also involved a larger proportion of nutritionally valuable insect prey. Males are aware of their paternity success, apparently because of their relative access to females prior to egg laying, and provide more paternal care at nests in which they are more likely to have sired young. Abstract : Copulations are rarely observed in the polygynandrous acorn woodpecker. However, cobreeder males that attend the breeder female prior to egg laying are more likely to sire nestlings and provide significantly more paternal care at the subsequent nest. Males apparently assess their probability of paternity based on access to females and increase their paternal behavior when they are more likely to have sired young.